2019
DOI: 10.21827/jdbsc.5.32575
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Communication Assistive Technology for Individuals with Deafblindness: A Case Study

Abstract: The main goal of this study was to evaluate a communication assistance device (CAD) for individuals with deafblindness, based on a braille display notetaker connected via Bluetooth to an iPhone. This study examined the use of this device by a 61-year-old woman living with Usher syndrome with sighted and hearing interlocutors during three restaurant outings.The study had three specific objectives: 1) To evaluate the participant's and her interlocutors' perceptions of their productivity in the communication inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(35 citation statements)
references
References 1 publication
(1 reference statement)
0
32
0
3
Order By: Relevance
“…The study conducted by Emerson and Bishop (2012) on the use of videophone technology received a high score of 7. Two other articles (Cantin et al, 2019;Ozioko et al, 2020) received a score of 3, due to limitations to data extraction, interpretation and coherence between the various methodological stages. The above-mentioned articles were categorized as qualitative research.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The study conducted by Emerson and Bishop (2012) on the use of videophone technology received a high score of 7. Two other articles (Cantin et al, 2019;Ozioko et al, 2020) received a score of 3, due to limitations to data extraction, interpretation and coherence between the various methodological stages. The above-mentioned articles were categorized as qualitative research.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Ozioko et al (2020) report a follow-up to Ozioko and Hersh (2015) showing the developmental process from stage 2 "concept" up to stage 4 "validation in a lab." Studies conducted by Cantin et al (2019), Emerson and Bishop (2012), and Evers et al (2012) are categorized in level 8 and 9, which indicated that the assistive technology was completed and implemented in field settings. In these studies, existing communication assistive technologies were adapted for use in daily communication with people with deafblindness.…”
Section: Technology Readiness Levelsmentioning
confidence: 99%
See 3 more Smart Citations